2023
DOI: 10.3390/ani13060965
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Somatic Cell Count and Milk Fatty Acid and Amino Acid Profile in Alpine and Saanen Goat Breeds

Abstract: The main goal of this study was to evaluate the relation of different SCC levels in goat milk with goat milk yield, milk composition, FA, and AA profiles. Whereas the investigated herd was composed of Alpine and Saanen goats, the influence of breed on milk parameters and milk yield was also assessed. The research was carried out in 2022 at a Lithuanian dairy goat farm with 135 goats (Saanen = 66 and Alpine = 69) without evidence of clinical mastitis. The current research revealed a relationship between SCC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The concentration of these fatty acids in goat milk also depends on their breed. Šlyžius et al [40] presented results that indicate that the concentration of C8:0 and C10:0 was significantly higher in Alpine goats' milk than in milk obtained from Saanen goats [40]. Moreover, Vulić et al [41], who also examined the milk of Alpine and Saanen goats, also reported the effect of breed on the concentration of caproic acid (C6:0).…”
Section: Fatty Acid Profile Of Bulk Tank Milk Samplesmentioning
confidence: 99%
“…The concentration of these fatty acids in goat milk also depends on their breed. Šlyžius et al [40] presented results that indicate that the concentration of C8:0 and C10:0 was significantly higher in Alpine goats' milk than in milk obtained from Saanen goats [40]. Moreover, Vulić et al [41], who also examined the milk of Alpine and Saanen goats, also reported the effect of breed on the concentration of caproic acid (C6:0).…”
Section: Fatty Acid Profile Of Bulk Tank Milk Samplesmentioning
confidence: 99%